Oribatid mites (Acari, Oribatida) in selected caves of the Kraków-Wieluń Upland (southern Poland) - Maślak, Magdalena; Barczyk, Gabriela (Biological Letters, 2011)
This paper describes and compares the species composition and community structure of the oribatid mite fauna of 5 caves in the Kraków-Wieluń Upland (Wyżyna Krakowsko-Wieluńska). We also compare oribatid communities in 3 chosen caves with oribatid communities in the soil and litter (leaves, dead wood, bat guano) in the vicinity of the cave entrances. Three hypotheses were tested: (1) oribatid communities from the soil and litter near the caves differ from the communities inhabiting caves; (2) the composition of oribatid communities depends on cave size; (3) the cave communities strongly depend on microhabitat quality and diversity. We collected 1112 adult oribatids from caves and 838 from the soil and litter near the caves. Oribatid communities in the caves were different from the soil communities. Litter, guano and dead wood were the microhabitats that affected oribatid communities significantly. In the other cave microhabitats (soil and mud), oribatids were infrequent. Cave size affected the oribatid community structure.